2006
DOI: 10.4028/www.scientific.net/msf.503-504.433
|View full text |Cite
|
Sign up to set email alerts
|

3D-Atom Probe Investigation of Vacancy Induced Interdiffusion during High Pressure Torsion Deformation

Abstract: Concentration gradients resulting from long range diffusion during Severe Plastic Deformation (SPD) have been investigated with the 3D Atom Probe technique (3D-AP). First, in a pearlitic steel where alloying elements (Mn, Si and Cr) are partitioned between the ferrite and carbides in the non-deformed state. After processing by High Pressure Torsion (HPT), they are homogeneously distributed in the nanostructure, indicating that long range diffusion occurred along with the dissolution of carbides. 3D-AP data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…(2)) because of active contribution of short-circuit diffusion as well as a significant increase in vacancy population. Related evidences for the reduction of Q were reported earlier with SPD-processed materials, especially at low temperatures [73][74][75][76].…”
Section: (I)supporting
confidence: 74%
See 1 more Smart Citation
“…(2)) because of active contribution of short-circuit diffusion as well as a significant increase in vacancy population. Related evidences for the reduction of Q were reported earlier with SPD-processed materials, especially at low temperatures [73][74][75][76].…”
Section: (I)supporting
confidence: 74%
“…However, a question arises if it is feasible for the decomposition to proceed within several minutes of HPT operation at ambient temperature. It is most conceivable that atomic diffusion must be accelerated by the HPT processing because of the generation of high-density lattice defects as reported in other papers [73][74][75][76]. In addition to the atomic diffusion, dynamic recovery and dynamic recrystallization also can affect the elemental decomposition.…”
Section: (I)mentioning
confidence: 95%
“…In such conditions, as demonstrated by Sato and co-authors [42], the migration energy of vacancies may be reduced by 30%. As suggested in our earlier studies, such conditions sufficiently enhance the diffusion rate of Fe in fcc Cu to account for bulk diffusion at room temperature [17,45]. However, the present investigations clearly show that at cryogenic temperature (77K) large amounts of homogeneous ssss can be obtained while the mobility of vacancies is not significant.…”
Section: (Ii) Alternative Diffusion Mediasupporting
confidence: 71%
“…2(d)). This indicates that even if some dislocations could act as diffusion pipe, the atomic mobility might be mostly enhanced by SPD induced vacancies [21].…”
Section: Figure 2: (A) Tem Bright Field Image and Related Saed Patter...mentioning
confidence: 98%
“…2(d)). This indicates that even if some dislocations could act as diffusion pipe, the atomic mobility might be mostly enhanced by SPD induced vacancies [21]. Previous studies on ball milled powders or sputtered thin films have demonstrated that phase separation in Cu-Cr SSSS starts in a temperature range of 400 to 500°C.…”
mentioning
confidence: 99%